Coronary angiography and percutaneous coronary intervention after transcatheter aortic valve replacement with medtronic self-expanding prosthesis: Insights from correlations with computer tomography. (15th October 2020) - Khan, Muhammad; Senguttuvan, Nagendra Boopathy; Krishnamoorthy, Parasuram; Vengrenyuk, Yuliya; Tang, Gilbert H.L.; Sharma, Samin K.; Kini, Annapoorna
Abstract: Objectives: We aim to describe the feasibility, challenges, success rates and techniques utilized in coronary angiography (CA) and percutaneous coronary intervention (PCI) in patients post transcatheter aortic valve replacement (TAVR). Background: CA and PCI after TAVR are becoming increasingly encountered in clinical practice. There have been technical difficulties reported in re-accessing the coronary arteries through the self-expanding CoreValve prosthesis. Methods: From January 2012 to November 2017, 672 patients who underwent TAVR with a self-expanding prosthesis were retrospectively reviewed and those who had a CA and/or PCI post TAVR were analysed. Clinical characteristics, angiographic and procedural details were obtained. A subgroup of patients had computed tomographic angiography (CTA) post TAVR to evaluate positions of the coronary ostia relative to the self-expanding prosthesis. Study endpoint was successful selective engagement of coronary ostia for CA and PCI. Results: Thirty-two patients (4.8%) had attempted 46 CA and 26 PCI after TAVR with a self-expanding valve. Mean age was 85.2 years and 41% were females. Selective left and right coronary angiography using standard catheters could be achieved in 50% and 28% of cases respectively. Successful PCI was performed in 25 cases (96%); however, significant technique modification was required in 64% of cases. CTA in 9 patients confirmed the difficulty in coronary re-access was due to a combination of the sealing skirt relationship to coronary ostia and sinotubular junction as well as commissural post orientation and significant native leaflet calcification. Conclusions: CA and PCI post TAVR with self-expanding CoreValve is technically challenging but feasible with modification of standard techniques. Highlights: Out of 672 patients who underwent TAVR with a self-expanding prosthesis, 32 patients (4.8%) had attempted 46 CA and 26 PCI Diagnostic angiography was done in 96% of cases; selective left and right coronary angiography was achieved in 50% and 28% of cases. Successful PCI was performed in 96% of the cases with significant technique modification required in 64% of cases. Computed tomographic angiography allowed to establish the anatomical factors associated with difficult coronary engagement.